2010
DOI: 10.1111/j.1365-2648.2010.05354.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV disclosure among HIV positive individuals: a concept analysis

Abstract: The proposed HIV disclosure attributes provide nursing scholars and researchers with new directions on how to reframe research questions, develop measurement tools to reflect better the diversity and fluidity of the process of HIV disclosure among HIV-positive individuals. Policy implications include the need to develop approaches that protect individual and public rights.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 50 publications
(95 reference statements)
0
41
1
Order By: Relevance
“…We identified 30 articles that contributed to the synthesis below, as well as two review articles, 7,18 one of which (15) was not specific to youth. Eight studies (Table 1) came from research conducted under the auspices of the ATN 8,9,[19][20][21][22][23][24] and four came from ATN's precursor, the REACH study, [25][26][27][28] an NIH-funded research network that recruited BHIV and HIV-uninfected at-risk youth ages 12-18 years, from 16 clinical care sites across the US between 1996 and 1999.…”
Section: Set Of Manuscriptsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 30 articles that contributed to the synthesis below, as well as two review articles, 7,18 one of which (15) was not specific to youth. Eight studies (Table 1) came from research conducted under the auspices of the ATN 8,9,[19][20][21][22][23][24] and four came from ATN's precursor, the REACH study, [25][26][27][28] an NIH-funded research network that recruited BHIV and HIV-uninfected at-risk youth ages 12-18 years, from 16 clinical care sites across the US between 1996 and 1999.…”
Section: Set Of Manuscriptsmentioning
confidence: 99%
“…Disclosure is itself a complex process, involving the interplay of social context, personal experiences, and relationship characteristics with decisions about whether/how/when/to whom to communicate one's HIV status, and related issues. 18 Disclosure has been labeled a ''major hurdle'' for youth living with HIV, 34 and doing so with sex partners is consistently cited as a major concern of theirs, particularly for BHIV. 30,42,46 Studies in primarily BHIV youth populations have reported prevalence of nondisclosure to recent sex partners of 40% 20 and 48%.…”
Section: Characteristics Of Sex Partners and Relationshipsmentioning
confidence: 99%
“…They implied, thus, that a scientifically developed concept is the essential first step in any research process. Concepts are viewed as the building blocks with which theory can be constructed, and their analysis is considered essential if the concepts are to be actively and correctly operationalised (Eustace & Ilagan 2010:2095Mikkelsen & Frederiksen 2011:1154. Walker and Avant (2011;2005:63-84) were leading pioneers in adapting theoretical work related to concepts for the discipline of nursing.…”
Section: Informationmentioning
confidence: 99%
“…One of the causes of lack of condom usage in sexual relationships is lack of awareness of the sex partner's status [6]. The disclosure of HIV status as a voluntary or non-voluntary decision is a complex process, in which the person reports his/her status of the disease along with the cause, time, and place [7]. The results of many studies indicate that the incidence rate of disclosure status of disease is between 32.7% and 92.7% and have also shown a negative reaction to women more than men [8].…”
Section: Introductionmentioning
confidence: 99%